VIEW OF UNDERSTANDING DYSPHEMISM AND ITS PRAGMATICS (KONFERENSIYA, 2025)
This article explores the often-overlooked linguistic phenomenon ofdysphemism, which are derogatory or offensive terms used to describe people,places, or things. While euphemisms soften the impact of words, dysphemismintentionally amplify their negative connotations. This abstract will outline thestructure of the article, which includes an introduction to dysphemism, their impacton communication and society, notable examples across different languages, andstrategies for addressing and mitigating their use